Collaborative Therapeutic Neuropsychological Assessment - Gorske, Tad T.; Smith, Steven R. (Springer New York : Imprint: Springer, 2009)
Collaborative Therapeutic Neuropsychological Assessment Edited by Tad T. Gorske, University of Pittsburgh, School of Medicine Steven R. Smith, University of California at Santa Barbara Perhaps the greatest challenge faced by neuropsychological assessment is its image as a bearer of bad news, i.e., the diagnosis of cognitive impairment. To meet this challenge and better address patient needs, practitioners need to fill the void that too often exists between diagnosis and treatment, starting with exchanging feedback about test results. The contributors to Collaborative Therapeutic Neuropsychological Assessment have developed methods that expand on traditional information-gathering means to build rapport with patients and let their voices be heard in decision-making: this client-centered approach has shown to lead to more personal interventions, better compliance, and stronger recovery. In contrast with other books in the field, this reader-friendly volume provides detailed methods and procedures on client feedback as well as assessment, in addition to conceptual and practical basics: The CTNA model and its underlying assumptions. The history and development of client-centered feedback in assessment, especially its roots in motivational interviewing. Empirical literature review, including the latest research on CTNA methods. Guidelines for conducting collaborative interviews in CTNA. Basic method for conducting collaborative feedback sessions in CTNA. Practical suggestions for using CTNA in clinical, rehabilitative, school, and other settings, and adapting the method to specialized populations such as children, the elderly, and minorities. Case studies illustrating salient concerns and techniques. The clinical knowledge presented in Collaborative Therapeutic Neuropsychological Assessment builds on the centrality of assessment in care to signal potent new directions in practice and training. As such, it deserves to be read by neuropsychologists (as well as rehabilitation, clinical, and school psychologists), and used in courses and certification programs in psychological and neuropsychological assessment.